Survival probabilities of loggerhead sea turtles (Caretta caretta) estimated from capture-mark-recapture data in the Mediterranean Sea - Paolo Casale; Antonios D. Mazaris; Daniela Freggi; Roberto Basso; Roberto Argano (Scientia Marina, 2007)
Survival probabilities of loggerhead sea turtles (Caretta caretta) are estimated for the first time in the Mediterranean by analysing 3254 tagging and 134 re-encounter data from this region. Most of these turtles were juveniles found at sea. Re-encounters were live resightings and dead recoveries and data were analysed with Barker’s model, a modified version of the Cormack-Jolly-Seber model which can combine recapture, live resighting and dead recovery data. An annual survival probability of 0.73 (CI 95% = 0.67-0.78; n=3254) was obtained, and should be considered as a conservative estimate due to an unknown, though not negligible, tag loss rate. This study makes a preliminary estimate of the survival probabilities of in-water developmental stages for the Mediterranean population of endangered loggerhead sea turtles and provides the first insights into the magnitude of the suspected human-induced mortality in the region. The model used here for the first time on sea turtles could be used to obtain survival estimates from other data sets with few or no true recaptures but with other types of re-encounter data, which are a common output of tagging programmes involving these wide-ranging animals.